Integrating Experiential Learning and Kahoot: Impacts on Elementary Students’ Science Knowledge and Scientific Attitudes - Dewi, Ni Putu Wulan Pratami; Jampel, I Nyoman; Candiasa, I Made (Universitas Pendidikan Mandalika, 2026)
This study aims to examine the effect of a Kahoot-assisted experiential learning model on students’ IPAS knowledge competence and scientific attitudes. The study employed a quantitative quasi-experimental method using a posttest-only control group design. Two classes were randomly assigned to the experimental and control groups. Data were collected using an IPAS knowledge competence test and a scientific attitude questionnaire and were analyzed using multivariate analysis of variance (MANOVA). The results revealed a statistically significant effect of Kahoot-assisted experiential learning on both outcome variables. The experimental group achieved higher mean scores in IPAS knowledge competence (86.35) and scientific attitudes (85.87) compared to the control group (82.56 and 60.56, respectively). These findings confirm that integrating experiential learning with Kahoot as an interactive digital medium enhances students’ conceptual understanding and scientific attitudes. In the context of elementary education in the digital era, this suggests that digital technology can play a more substantive role beyond merely increasing classroom engagement. When aligned with an appropriate pedagogical model, such as experiential learning, interactive digital media can facilitate meaningful learning experiences that promote conceptual mastery, active participation, reflection, and the development of positive scientific attitudes. Therefore, this integration provides a promising direction for elementary science instruction, particularly in addressing the need for innovative and pedagogically grounded digital learning practices in 21st-century classrooms.